1991
DOI: 10.1097/00006842-199105000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Hamsters with coronary vasospasm are at increased risk from stress.

Abstract: Results of earlier experiments suggested that hamsters with inherited heart disease were at a higher risk of succumbing to stress during the vasospastic, lesion-forming period of their lives rather than later when the process of congestive heart failure had begun. To test this hypothesis, we stressed cardiomyopathic hamsters (CMH) whose ages differed by about 3 months; the younger of the two groups of stressed hamsters was in the vasospastic phase of the disease. The stressor was cold immobilization in which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Other animal models have been utilized to study the effects of stress on hearts with preexisting disease. In this regard, a series of studies (Natelson et al 1991, McCabe et al 2000 demonstrated that stress could worsen the effects of heart failure and cardiac death in a hamster model with inherited heart disease. With regard to cardiac arrhythmias and sudden death, studies by Verrier and colleagues (Verrier & Lown 1984) have shown that stress can lower the threshold for malignant arrhythmias in dogs with induced coronary artery blockage.…”
Section: Animal Model Studiesmentioning
confidence: 99%
“…Other animal models have been utilized to study the effects of stress on hearts with preexisting disease. In this regard, a series of studies (Natelson et al 1991, McCabe et al 2000 demonstrated that stress could worsen the effects of heart failure and cardiac death in a hamster model with inherited heart disease. With regard to cardiac arrhythmias and sudden death, studies by Verrier and colleagues (Verrier & Lown 1984) have shown that stress can lower the threshold for malignant arrhythmias in dogs with induced coronary artery blockage.…”
Section: Animal Model Studiesmentioning
confidence: 99%
“…The BIO 14:6 Syrian cardiomyopathy hamster (CMH) is a widely used model of both cardiac and skeletal abnormalities (Kagiya et al , 1991; Davidoff & Gwathmey, 1994). Abnormal cellular calcium homeostasis and spasms of the microcirculation, producing transient focal ischaemia, have been postulated to be at the origin of the cell death in these animals (Natelson et al , 1991; Conway et al , 1994). In the heart, cell loss is associated with compensatory ventricular hypertrophy and the degree of hypertrophy correlates with the myosin isoform restructuring (see Kitsis & Scheuer, 1988; Lompré et al , 1991 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, different stressor intensities produced different survival curves in 2.5-and 5-month CMHs; younger hamsters, in their lesion-forming period, were at an increased risk from stress (9). These data suggested that stressor intensity may play an important role in pathological outcomes of hamster heart disease following stress.…”
mentioning
confidence: 85%